Decentralized Attestation and Distribution of Information Using Blockchains and Multi-Protocol Storage - Harer, Felix; Fill, Hans-Georg (IEEE access, 2022)
The distribution of information through web protocols is today based on the client-server model. Recently, decentralized protocols with greater availability appear as well as blockchain-based attestation methods, allowing for proving the existence of information. In combination, these methods promise a secure, decentralized and long-term storage. However, there exist two major problems: (1) the scalability of blockchains limits their storage capacity and (2) various (de)centralized web protocols are in use and could alleviate this problem, but they do not support blockchain-based attestations. In this paper, we extend an approach for blockchain-based attestation with compatibility for multi-protocol storage. Instead of specific protocols or blockchains, the extended approach aims to contribute novel concepts to the discussion on blockchain scalability. It augments the capabilities of existing protocols for applications such as certification or timestamping of digital artifacts. With the use of decentralized protocols such as IPFS, further availability and inherent resilience properties are gained, allowing for applications such as open research repositories and digital registries. We discuss the architecture of the extended approach, a possible implementation in a smart contract on the Ethereum blockchain with IPFS and Git, and evaluate the time and cost of attestations.